2014
DOI: 10.1021/ac502823e
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Sulfur Species in Coals from the Argonne Premium Sample Program by Solid Sampling Electrothermal Vaporization Inductively Coupled Plasma Optical Emission Spectrometry

Abstract: A new direct solid sampling method for speciation of sulfur in coals by electrothermal vaporization inductively coupled plasma optical emission spectrometry (ETV-ICP OES) is presented. On the basis of the controlled thermal decomposition of coal in an argon atmosphere, it is possible to determine the different sulfur species in addition to elemental sulfur in coals. For the assignment of the obtained peaks from the sulfur transient emission signal, several analytical techniques (reflected light microscopy, sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…For example, the quantication of halogens (chlorine, bromine) in coal was studied, 50,56 as well as total oxygen content 58 (a parameter conventionally not accessible via ICP techniques), and sulphur. 12,59 In case of metallic samples, not only trace impurities were analyzed, 11,60 but also chlorine, 47 as well as the isotopic composition of the matrix metal tungsten. 44 Synthetic organic materials such as polymers and pharmaceutical components were analyzed for the presence of trace elements 42,51,61 as well as for bromine.…”
Section: Application Examplesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the quantication of halogens (chlorine, bromine) in coal was studied, 50,56 as well as total oxygen content 58 (a parameter conventionally not accessible via ICP techniques), and sulphur. 12,59 In case of metallic samples, not only trace impurities were analyzed, 11,60 but also chlorine, 47 as well as the isotopic composition of the matrix metal tungsten. 44 Synthetic organic materials such as polymers and pharmaceutical components were analyzed for the presence of trace elements 42,51,61 as well as for bromine.…”
Section: Application Examplesmentioning
confidence: 99%
“…By applying a slow heating ramp in the ETV system, the authors demonstrated that it is possible to distinguish between those two aluminum-containing phases and to obtain quantitative information about the phases, apart from the mere total aluminum content of the sample which is obtained aer digesting the sample. Bauer et al 12 showed that different sulphur species present in coal can be effectively distinguished from one another, since they exhibit different volatility. This can help in choosing appropriate coal treatment strategies to reduce the concentration of sulphur in the coal prior to combustion (the sulphur-reduced coal can then be considered as "functional" raw material, as its initial properties were changed to obtain better performance).…”
Section: Temporal Separation Of Sample Constituents With Different Vomentioning
confidence: 99%
See 1 more Smart Citation
“…The determination of S was also represented in this section with a couple of papers proving interesting. A paper on S species in coals from the Argonne was presented by Bauer et al 40 The authors described a new direct solid sampling method for speciation of S in coals using electrothermal vaporization (ETV)-ICP-OES. Coal was decomposed in an argon atmosphere using controlled thermal decomposition to determine the different S species in addition to elemental S. The described method is time and cost effective and well suited for the fast characterization of S species in coal.…”
Section: Fuels and Lubricantsmentioning
confidence: 99%
“…Alternatively, laser ablation inductively coupled plasma isotope dilution mass spectrometry (LA-ICP-IDMS), 12 electrothermal vaporization (ETV), inductively coupled plasma optical emission spectrometry (ICP OES) and ETV inductively coupled plasma mass spectrometry (ICP-MS) 13 have been also used for the determination of sulfur, sulfur species and halogens. 14 Additionally, the determination of sulfur can be performed using spectrometric (ICP OES or ICP-MS) or chromatographic (ion chromatography (IC) with conductivity detection) techniques. However, these techniques conventionally require bringing the analyte into an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%